Flume and single-pass washing systems for fresh-cut produce processing: Disinfection by-products evaluation. (March 2022) - Zhang, Tianqi; Lee, Wan-Ning; Luo, Yaguang; Huang, Ching-Hua
Abstract: Free chlorine is widely used in fresh-cut produce washing to minimize microbial cross-contamination, but its application can also lead to the formation of harmful disinfection byproducts (DBPs). This study compared DBPs in process water and washed produce during commercial operation. Samples of shredded lettuce and diced cabbages washed in chlorinated water in the traditional double-flume wash and novel immersion-free single-pass wash systems were collected at multiple time points and locations from the processing lines. A suite of 33 conventional and emerging DBPs, including 4 trihalomethanes (THMs), 9 haloacetic acids (HAAs), 9 nitrogenous DBPs (N-DBPs), and 11 carbonaceous DBPs (C-DBPs), were investigated. Overall, N-DBPs and HAAs dominated the concentration of detected DBPs. Wash water in the flumes contained 7–111 folds higher DBP levels compared to that in the single-pass system, with the abundance of DBPs following the order of N-DBPs > HAAs > C-DBPs > THMs. DBPs were detected on washed produce, presenting primarily in the forms of N-DBPs and HAAs followed by C-DBPs and THMs. While higher levels of DBPs were detected in flume-washed produce, the final potable water rinse significantly reduced the DBP concentration in these products. The concentrations of THMs and HAAs on these washed products were used to estimate potential exposure via consumption of fresh-cut produce and the levels were below the daily allowable exposure for drinking water standard established by the U.S. Environmental Protection Agency. The detected high concentration and potential toxicity of N-DBPs indicate the need for further research. The findings of this study advance the understanding of the formation and removal of DBPs during wash processes, and identify additional research opportunities for further reduction in DBPs and food safety improvement. Highlights: DBP level higher in wash water from flume wash than from single-pass wash. DBP level higher in washed produce from flume wash than from single-pass wash. Final potable water rinse reduced DBP concentration in flume washed produce. N-DBPs and HAAs dominated DBP concentrations in wash water and washed produce. Potential exposure to HAAs assessment provides insight for future research directions regarding N-DBPs.